1992
DOI: 10.1063/1.858394
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the inelastic interaction of unequal vortices in two-dimensional vortex dynamics

Abstract: The interaction of two isolated vortices having uniform vorticity is examined in detailed contour dynamics calculations, and quantified using a diagnostic that measures the coherence of the final state. The two vortices have identical vorticity, leaving two basic parameters that determine the evolution: the radius ratio and separation distance. It is found that the term "vortex merger" inadequately describes the general interaction that takes place. Five regimes are found: (1) elastic interaction, (2) partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
211
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(223 citation statements)
references
References 26 publications
11
211
1
Order By: Relevance
“…Before the merger, the radius of MC-A was 0.78 km and that of MC-B 0.48 km, and the distance between the two misocyclones was 1.8 km at 15:08 JST. Using these values and the method of Dritschel and Waugh (1992), we estimated that the diameter after the merger should be approximately 1.05 times that before the merger. By comparison, the observed diameter of MC-A at 15:08 JST (before the merger) was 1.55 km, and at 15:14 JST (after the merger) it was 1.45 km; thus, the diameter after the merger was about 0.94 times that before the merger, slightly less than the diameter estimated by the method of Dritschel and Waugh (1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the merger, the radius of MC-A was 0.78 km and that of MC-B 0.48 km, and the distance between the two misocyclones was 1.8 km at 15:08 JST. Using these values and the method of Dritschel and Waugh (1992), we estimated that the diameter after the merger should be approximately 1.05 times that before the merger. By comparison, the observed diameter of MC-A at 15:08 JST (before the merger) was 1.55 km, and at 15:14 JST (after the merger) it was 1.45 km; thus, the diameter after the merger was about 0.94 times that before the merger, slightly less than the diameter estimated by the method of Dritschel and Waugh (1992).…”
Section: Resultsmentioning
confidence: 99%
“…We applied the method of Dritschel and Waugh (1992), who used two-dimensional vortex dynamics to predict the vortex radius following a merger from the ratio of the two pre-merger vortex radiuses and the distance between them before the merger, to estimate the radius of the vortex resulting from the merger. Before the merger, the radius of MC-A was 0.78 km and that of MC-B 0.48 km, and the distance between the two misocyclones was 1.8 km at 15:08 JST.…”
Section: Resultsmentioning
confidence: 99%
“…The snapshots illustrate distinct stages of the transformation from turbulence to hurricane, but do not tell the complete story. The early stage involves 2D processes of self-organization, such as the coalescence of like-sign vorticity through mergers and more subtle mechanisms (Melander et al, 1988;Carnevale et al, 1991;Dritschel and Waugh, 1992;Lansky et al, 1997;Dubin, 1999,2001;Schecter, 2003). Mesoscale cyclones progressively dominate anticyclones.…”
Section: Genesis Over a Cool Ocean At 10 • Nmentioning
confidence: 99%
“…For the purposes of this study, t * de,2 is estimated using the velocity gradient tensor [3]. We consider the classifications developed for inviscid asymmetric vortex interactions [12,5] All interactions eventually result in a single vortex. In complete merger, the circulation of the final compound vortex is greater than that of either original vortex.…”
Section: Merging Criterionmentioning
confidence: 99%
“…In the more general interaction of two unequal size and/or strength (asymmetric) vortices, there is a greater range of flow behavior and the interaction may result in the destruction of the smaller/weaker vortex. Previous inviscid flow studies have identified distinct flow regimes based on the efficiency of the interaction [5,12]. Elastic interaction occurs when there are only small deformations and essentially no change in circulation of the vortices.…”
Section: Introductionmentioning
confidence: 99%